Motivation of Officials’ in the System of Governmental Work - Glova, I. V. (Psychological Prospects Journal, 2011)
The problem of interconnection of effective governmental system and professional motivation of officials is described in this article. The analysis is carried out my means of motivational diagnosis of official’s. As the result of this analysis the motivational profile of official’s was outlined. The ways of development of professional motivation is described.
Keywords: state administration official, professional motivation motivational profile of an official